the MANAJAMEN KONSTRUKSI PADA GEDUNG HOTEL AL – HAJJ DELAPAN LANTAI DI JALAN LETNAN JENDRAL SUTOYO, KOTA PONTIANAK - Farhanika, Annisha Syalwalia; Agus, watini; Fitriani, Nurul (Jurusan Teknik Sipil Polnep, 2022)
The author carried out construction management planning on the Eight Story Al - Hajj Hotel Building on Letnan Jendral Sutoyo Street, Pontianak City, which had previously been carried out structural planning and plans by Achmad Idris Setianto and Nurianda Rantau Nika in 2020. Therefore, to realize the construction of the Al - Hajj Hotel Building, proper construction management planning is needed, so that the construction process of this hotel runs smoothly, on time, efficiently and the desired quality can be achieved. Therefore, the author plans a construction management system for the construction of the Al - Hajj Hotel Building which is used as the title of this research. The method used in this construction management discussion is the management system of cost, quality, time, Human Resources (HR) and Occupational Health and Safety (OHS) on structural work which includes foundations, beams, columns and floor plates. Based on the results of the analysis of the method above, the cost of preparatory work and the structure required in the completion of the Al - Hajj Hotel Building construction project is Rp. 43,925,525,000 and can be completed within 30 weeks or 272 calendar days. For quality planning, the results are form of quality control and a list of specification tables. In Human Resources (HR) planning is number of labor needs as a means for good work implementation and in the planning of OHS management planning is form of identification and control of potential OHS hazards to each type of work and the cost for the needs of Personal Protective Equipment (PPE) and Work Protective Equipment (WPE) amounted to Rp. 87,155,000.